Sliding mode vibration control of Euler–Bernoulli beam with unknown bounded disturbances. (December 2021) - Ma, Yifei; Lou, Xuyang; Wu, Wei
Abstract: This paper is concerned with the sliding mode boundary control of an Euler–Bernoulli beam with external unknown bounded disturbances. For the beam system with unknown bounded disturbances, the main control goal lies in reducing the influence of the disturbances and suppressing the vibration of the beam. Firstly, the sliding mode function and sliding surface are constructed by boundary output signals. Secondly, a sliding mode boundary controller is proposed by introducing the sliding mode function. With the proposed controller, the finite time to reach the sliding surface is achieved and the uniform boundedness of the beam system is guaranteed. Finally, the effectiveness and advantages of the proposed results are demonstrated through simulations. Graphical abstract: Highlights: A sliding mode boundary controller is proposed to suppress the vibration of an Euler–Bernoulli beam. The finite time to reach the sliding surface is derived and the uniform boundedness is guaranteed. The sliding mode boundary controller only needs boundary signals.